THE SOCIOLOGY OF ISLAM : KNOWLEDGE, POWER AND CIVILITY - Salvatore, Armando, author (Hoboken, N.J. : Wiley, 2016)
The Sociology of Islam provides an accessible introduction to this emerging field of inquiry, teaching and debate. The study is located at the crucial intersection between a variety of disciplines in the social sciences and the humanities